Aplicación móvil para mejorar la enseñanza de la lengua ikitu en el colegio Liceo Naval Capitán de Navío Francisco Carrasco de la ciudad de Iquitos, 2020 - Chuje Panaifo, Franz Ghusept (2020)
The results of the research carried out in the context of this thesis are presented, which determined the development and validation of a mobile application conceptualized as an educational tool oriented towards the learning of the Ikitu language. The study population was the teachers of the school "Liceo Naval Capitán de Navío Francisco Carrasco" in the city of Iquitos. The results obtained have demonstrated the effectiveness of the use of the "Quimaya" application (which means child, in the Ikitu language), in the teachers, enabling them to learn basically up to 63% of the contents, of categories such as "Alphabet", "Numbers", "Colours", "Expressions", "Human Body", "Flora", "Fauna" and "Things". Likewise, there was a high acceptance by teachers in the use of the mobile application, and the contents presented. It was concluded that the use of a mobile application is a useful tool that improves language learning processes, and is an easily understood tool that can be replicated to support distance education in native languages, given the context of the COVID-19 pandemic, while at the same time disseminating and promoting Peruvian Amazonian cultures.